Risk of Cesarean With Obesity and Advancing Maternal Age [5C]. (May 2017) - Petersen, Shariska; Khangura, Raminder; Fitzgerald, Michael; Sousa, Denise; Goyert, Gregory
Abstract : INTRODUCTION: The objective of this study is to examine the impact of obesity on cesarean birth rate in an older group of primigravid women. METHODS: This retrospective study analyzed data on nulliparous women over 34 years of age who delivered between January 2013 and July 2016 at a single institution. Abstracted data included: BMI, gestational age at delivery, mode of delivery, spontaneous or induced labor, indication for cesarean, and co-morbidities (chronic hypertension, diabetes, preeclampsia, IUGR). RESULTS: One hundred thirty one patients were included. Obesity rate was 48% (BMI greater than 30kg/m 2 ) with a mean maternal age of 37.5 years. The overall C/S rate was 61.8% (81/131). Twenty-seven patients had c/s prior to active labor, 31 were associated with labor induction, and 23 were associated with spontaneous labor. Obese patients had a 122% increase odds of cesarean birth, compared to those with a BMI at or below 30. For every one unit increase in BMI, there was a 7% increase in the odds of cesarean birth. Obese African American patients had a 141% increase odds of cesarean birth when compared to all other groups. For all groups, the most common indication for cesarean section was non-reassuring fetal status. CONCLUSION: This population confirms the association of increasing BMI with higher C/S rates and this is exaggerated in older nulliparous women. The further increase in rate in African American patients may be related to the increased incidence of clinically significant fibroids associated with malpresentation or obstruction and warrants further study to enhance our counseling for these patients.